The Oxford handbook of business and the natural environment - Bansal, Pratima; Hoffman, Andrew J., 1961- (Oxford : Oxford University Press, 2012)
This handbook discusses the main issues, research, and theory on business and the natural environment, and how they impact on different business functions and disciplines.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Industrial management -- Environmental aspects -- Europe; Environmental responsibility -- Europe